Factors Influencing Investor’s Decision Making in Nepalese Commercial Banks: Moderating the Role of Locus of Control - Shrestha, Narendra Kumar (KIC International Journal of Social Science and Management, 2024)
This study examines how investors’ demographic characteristics-such as age, gender, education, and experience and their investment choices are related with bias, and representational bias-serving as mediators in Nepalese commercial banks. A structured questionnaire survey was used to collect data from 403 participants who worked for various commercial banks in Nepal. To investigate the ways in which behavioral aspects and demographic traits influence investing decisions, a multiple regression analysis was performed. Herd behavior, locus of control, availability biases, and representative biases all have a big impact on investing choices. Furthermore, investing decisions are positively and significantly impacted by age, gender, and educational attainment. Experience is not a significant factor, though more seasoned investors typically depend less on emotional cues. The study’s conclusions offer direction for the growth of the Nepalese stock market as well as insights into typical investor behavior patterns.